Overview of Core Beliefs in Victims of Sexual Harassment - Mashur, Muhammad Taufik; Hamid, Harlina; Fakhri, Nur Fitriany (Polteknik Ilmu Pemasyarakatan, 2025)
Sexual harassment is a sexually oriented act committed against another person that results in the emergence of displeasure or compulsion from the act. Victims of sexual harassment have their impacts on the victims, ranging from physical, and psychological to social so that what victims of sexual harassment experience influences their core beliefs in living their lives. These core beliefs are formed through experiences since childhood, the living environment, and the subject's interactions with the world and other people. This research aims to find out what the core beliefs of victims of sexual harassment are and the impact of the harassment incident. This research was conducted using qualitative methods with a case study approach. The research respondents, namely two women, were victims of sexual harassment who used purposive sampling techniques and used significant others to obtain relevant data. Data collection uses interviews, documentation, and core belief inventory (CBI). The research results show that the core beliefs developed by the two respondents are different. The first respondent showed a negative core belief and the second respondent showed a positive core belief so that if the core belief is positive, it will give rise to positive intermediate beliefs and automatic thoughts and vice versa. These things influence the way of life of each of the two respondents. The impact felt by the two respondents was anxiety, fear and even blaming themselves. This research was implemented to provide an overview of the core beliefs held by victims of sexual harassment and the impact felt by victims of harassment.